The historical role of kazakh language in the system of turkic languages (Eurasian Journal of Philology Science and Education, 2021)
The article touches upon the historical role of Kazakh language in the system of Turkic languages, as the former passed on its own way to the formation of different subethnical processes which lasted for several centuries. It comes as no surprise that it is necessary to know well the nature of the given ethnos itself to study any ethnic language. The knowledge of only internal language laws is not sufficient to recognize the original nature of any ethnic language and it goes without saying that its ultimate roots is directly related to the culture, history, religion and way of living of the ethnic groups speaking this language for centuries. Therefore, the way of study the national language through the combined research of the ethnic language, culture and cognition, and the history led to the birth of the totally new directions in the field of linguistics as anthropolinguistics, psycholinguistics and cognitive, social linguistics. The language of that time, which formed the basis of the ethnogenesis of Kazakh people who contributed to the formation of the nation were applied by the tribes and people are considered as the historical basis of modern Kazakh language. As a result of combining and merging all related tribal groups included in the territories of the Kazakh Khanate (Uysin, Kanlу Kipchak, Argyn, Dulat, Shapirashty, Zhalayr, Sirgeli, Alban, Suan, Konyrat, Nаyman, Kerey, Alshyn etc.) formed a monolithic integration of national Kazakh language and acquired a general structure of language. The aim of the research is to define the historical role of Kazakh language in the system of Turkic languages